2022
DOI: 10.4103/jcecho.jcecho_14_22
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous hypertrophy of the interatrial septum: A case report and insights from the literature

Abstract: Lipomatous hypertrophy of the interatrial septum (LHIS) is a histologically benign cardiac lesion that is defined by excessive fat accumulation in the area of the interatrial septum (IAS) that does not include the fossa ovalis. Another unusual illness is lipomatosis, which is defined as a broad overgrowth of mature adipose tissue that involves a large portion of an extremity or trunk. We describe a rare case with significant LHIS accompanied by subcutaneous lipomatosis. Echocardiography revealed a mass in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Cardiac magnetic resonance describes the same aspect of a clearly defined mass, with a characteristically high-intensity signal in T1-weighted images with mild inhomogeneous late gadolinium enhancement, highlighting fat accumulation [22]. A clear differentiation between adipose and muscular tissue can be made, as both blood and adipose tissues have a high T1/T2 ratio, providing a strong signal, whereas the myocardium has a low ratio, thus providing a low signal [5]. The same aspect was described in our case.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 97%
See 3 more Smart Citations
“…Cardiac magnetic resonance describes the same aspect of a clearly defined mass, with a characteristically high-intensity signal in T1-weighted images with mild inhomogeneous late gadolinium enhancement, highlighting fat accumulation [22]. A clear differentiation between adipose and muscular tissue can be made, as both blood and adipose tissues have a high T1/T2 ratio, providing a strong signal, whereas the myocardium has a low ratio, thus providing a low signal [5]. The same aspect was described in our case.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 97%
“…Several authors reported the same suboptimal defined aspect, requiring a better visualization of the IAS. Licordari R. et al demonstrated a right atrial mass with no clear definition in a 55-year-old patient also suffering from hypertension, obesity, and subcutaneous lipomatosis [5]. Lampropoulous K.M.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations